Amyloid, Crohn’s disease, and Alzheimer’s disease - are they linked? - Duda-Madej, Anna; Stecko, Jakub; Szymańska, Natalia; Miętkiewicz, Agnieszka; Szandruk-Bender, Marta (Frontiers in Cellular and Infection Microbiology, 2024)
Crohn’s disease (CD) is a chronic inflammatory disease that most frequently affects part of the distal ileum, but it may affect any part of the gastrointestinal tract. CD may also be related to systemic inflammation and extraintestinal manifestations. Alzheimer’s disease (AD) is the most common neurodegenerative disease, gradually worsening behavioral and cognitive functions. Despite the meaningful progress, both diseases are still incurable and have a not fully explained, heterogeneous pathomechanism that includes immunological, microbiological, genetic, and environmental factors. Recently, emerging evidence indicates that chronic inflammatory condition corresponds to an increased risk of neurodegenerative diseases, and intestinal inflammation, including CD, increases the risk of AD. Even though it is now known that CD increases the risk of AD, the exact pathways connecting these two seemingly unrelated diseases remain still unclear. One of the key postulates is the gut-brain axis. There is increasing evidence that the gut microbiota with its proteins, DNA, and metabolites influence several processes related to the etiology of AD, including β-amyloid abnormality, Tau phosphorylation, and neuroinflammation. Considering the role of microbiota in both CD and AD pathology, in this review, we want to shed light on bacterial amyloids and their potential to influence cerebral amyloid aggregation and neuroinflammation and provide an overview of the current literature on amyloids as a potential linker between AD and CD.